Speaking volumes : orality and literacy in the Greek and Roman world - Watson, Janet. (Mnemosyne, Supplements, 2001)
This volume examines orality and literacy in the ancient Greek and Roman world through a range of perspectives and in various genres. Four essays on the Homeric epics present recent research into performative aspects of language, cognitive theory and oral composition, a re-evaluation of Parry's oral-formulaic theory, and a new perspective on the poem's transmission. These are complemented by studies of the oral nature of Greek proverbial expressions, and of poetic authority within a fluid oral tradition. Two essays consider the significance of the written word in a predominantly oral culture, in relation to star calendars and to Panathenaic inscriptions. Finally, two chapters consider the ongoing influence of oral tradition in the ancient novel and in Roman declamation. These essays illustrate the importance of considering ancient texts in the context of fluctuating oral and literate influences.